Prognoza zapotrA Forecast of the Demand for Places in Social Care Homes in the Greater Poland Voivodeship and Key Conditions forzebowania na miejsca w domach pomocy społecznej w województwie wielkopolskim i najważniejsze uwarunkowania zaspokojenia potrzeb - Grygiel, Grzegorz (Studia Oeconomica Posnaniensia, 2017)
An aging society, which is caused by the lengthening of the average human life span as well as lower birth rate, determines the development of a long-term care system. With age, elderly people are struggling with their daily activities. Over time assistance received from families or local communities may be insufficient, which can lead to directing a dependent person to an all-day care institution. Social care homes are a form of institutional support. These homes are dedicated for those, who lack the necessary help and assistance in their dwelling-places. These institutions are providing help, support, elicitation and rehabilitation to, inter alia, elderly people. An estimated number of social care home residents, who are over 75 years old, indicate that a demand for places in these homes will grow in the coming years. An increased requirement for places in all-day care institutions will become a significant financial burden for local government units. A growing number of people needing institutional help should result in an increase in the number of places in existing social care homes or building new ones. The above rationale constitutes a starting point for a debate on the future founding of benefits for elderly and/or dependent people.